Erratum to "Direction dependent strong magnetoelectric coupling in La0.7Ba0.3MnO3 embedded poly(vinylidenefluoride-co-trifluoroethylene) flexible nano-composite films at room temperature" Scripta Materialia, Volume 189, December 2020, Pages 30-35/Article Number-: SMM-SMM-20-738. (February 2021) - Koner, Sougata; Deshmukh, Pratik; Khan, Azam Ali; Ahlawat, Anju; Karnal, A.K.; Satapathy, S.
Graphical Abstract: Image, graphical abstract